2020
DOI: 10.3389/fpsyg.2020.00537
|View full text |Cite
|
Sign up to set email alerts
|

Factor Structure of the 10-Item Perceived Stress Scale and Measurement Invariance Across Genders Among Chinese Adolescents

Abstract: Background: Chinese adolescents encounter a lot of stressors, such as academic burden and parental pressure. However, little is known about their perception of stress. The 10-item Perceived Stress Scale (PSS-10) is a widely used instrument to measure individuals' appraisal of global stress in academic research and clinical practice. The current study aimed to evaluate the best-fit factor structure model of the PSS-10 and the measurement invariance across genders in Chinese adolescents.Methods: A total of 1,574… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
79
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(95 citation statements)
references
References 79 publications
(105 reference statements)
13
79
0
3
Order By: Relevance
“…The total score of this scale ranges from 10 to 50, and the higher the score, the higher the degree of perceived stress. In this study, the Cronbach's alpha coefficient was 0.79, and the scale has shown good reliability and validity in prior studies (64)(65)(66).…”
Section: Perceived Stressmentioning
confidence: 59%
“…The total score of this scale ranges from 10 to 50, and the higher the score, the higher the degree of perceived stress. In this study, the Cronbach's alpha coefficient was 0.79, and the scale has shown good reliability and validity in prior studies (64)(65)(66).…”
Section: Perceived Stressmentioning
confidence: 59%
“…It is known to have established and acceptable psychometric properties. 13,14,25,26 Even though PSS has been widely used in dermatology in recent years, [27][28][29][30][31] except for the study by Hafsia et al, 10 it has not been used to assess the role of stress in cases of hand eczema, and hence is underutilised. In the present study, PSS scores was calculated for all the 62 participants and it was found that 42 (67.7%) of them had increased stress scores, of which 10 (6.1%)…”
Section: Resultsmentioning
confidence: 99%
“…Contrary to other scores which measure stress based on the stressful life events that had occurred in the life of a patient, PSS is a measure of the degree to which situations in one's life are appraised as stressful. It is known to have established and acceptable psychometric properties 13,14,25,26 . Even though PSS has been widely used in dermatology in recent years, 27‐31 except for the study by Hafsia et al, 10 it has not been used to assess the role of stress in cases of hand eczema, and hence is underutilised.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, when evaluating perceived stress, we are scoring a global response that depends on various personal traits such as coping mechanisms, baseline psychopathological state or personality types. However, perceived stress is a complex concept that depends on factors such as the perception of how self-effective the person is in coping with demands from the external environment and the perception of helplessness as an internal response to negative emotions and lack of control facing stress ( Liu et al, 2020 ). Different studies consider that the distinction between both dimensions represent separate components of the stress experience, so they should not be included in a single construct ( Baik et al, 2019 ; Liu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%